The changing balance of technology and process: A case study on a combined setting of model‐driven development and classical C coding. Issue 11 (17th March 2017) - Hebig, Regina; Derehag, Jesper
Abstract: The increasing flexibility in industry leads to an ecosystem of change, affecting the balance of processes and technology as well as the developers who have to cope with the change. Furthermore, the change itself might impact the ability to use quantitative methods to learn from previous experience. The goal of this study is to better understand the ecosystem of mutual impacts and changes of process and technologies as well as how developers perceive a technology setting and deal with its change. Therefore, we conducted a case study at Ericsson, performing a series of interviews among 6 employees (senior developers and architects). We identified a time line of changes that happened over 7 years. A set of observations about the relation between processes and tooling, and observations about developer's perceptions of the technology settings, and their strategy to deal with these changing technology settings. We discuss how the observed change impacts the ability to perform quantitative evaluations of technology and processes. The findings show that a bad choice of technologies can lead to unexpected impact on team dynamics. Furthermore, change happens so regular that it needs to be considered when collecting data for a quantitative evaluation of, eg, productivity. Abstract : The paper identifies a timeline of changes that happened over 7 years within the context of a product's software development. Results are a set of observations about the relation between processes and tooling and observations about developer's perceptions of the technology settings and their strategy to deal with these changing technology settings. It is discussed how the observed change impacts the ability to perform quantitative evaluations of technology and processes.